Pengaruh Kerjasama Tim dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Dana Purna Investama di Samarinda - Andi Assyifa Puspa Ningrum; Damingun; Bun Yamin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine and analyze how the influence of Teamwork and Job Satisfaction on employee performance at PT. Dana Purna Investma in Samarinda. This type of research is quantitative. The time of this research is April-June 2024. The population in this study were 51 employees of PT Dana Purna Investama. The sample taken using saturated sampling technique and obtained as many as 51 employees. Data was obtained from respondents using Google Form. This data analysis uses SPSS 30 to test validity, reliability, and multiple linear regression. The results of this study indicate that teamwork has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, and teamwork and job satisfaction simultaneously have a significant effect on employee performance at PT Dana Purna Investama